Identification of Novel Malaria Transmission-Blocking Vaccine Candidates - Takashima, Eizo; Tachibana, Mayumi; Morita, Masayuki; Nagaoka, Hikaru; Kanoi, Bernard N.; Tsuboi, Takafumi (Frontiers in Cellular and Infection Microbiology, 2021)
Control measures have significantly reduced malaria morbidity and mortality in the last two decades; however, the downward trends have stalled and have become complicated by the emergence of COVID-19. Significant efforts have been made to develop malaria vaccines, but currently only the RTS,S/AS01 vaccine against Plasmodium falciparum has been recommended by the WHO, for widespread use among children in sub-Saharan Africa. The efficacy of RTS,S/AS01 is modest, and therefore the development of more efficacious vaccines is still needed. In addition, the development of transmission-blocking vaccines (TBVs) to reduce the parasite transmission from humans to mosquitoes is required toward the goal of malaria elimination. Few TBVs have reached clinical development, and challenges include low immunogenicity or high reactogenicity in humans. Therefore, novel approaches to accelerate TBV research and development are urgently needed, especially novel TBV candidate discovery. In this mini review we summarize the progress in TBV research and development, novel TBV candidate discovery, and discuss how to accelerate novel TBV candidate discovery.